2015
DOI: 10.1097/mpg.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Therapy in Children With Crohn Disease Previously Treated With Infliximab

Abstract: In clinical practice, adalimumab induces remission in two-thirds of children with IFX refractory CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The literature search revealed 797 references in Pubmed and 1067 in Embase; however, some references were excluded, among other reasons, for duplication and non‐availability of data on the effectiveness of the second anti‐TNF . Finally, only 46 studies met the inclusion criteria and were included . Of these, 37 focused on CD (Tables S1 and S2), 8 on UC, and 1 on pouchitis (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search revealed 797 references in Pubmed and 1067 in Embase; however, some references were excluded, among other reasons, for duplication and non‐availability of data on the effectiveness of the second anti‐TNF . Finally, only 46 studies met the inclusion criteria and were included . Of these, 37 focused on CD (Tables S1 and S2), 8 on UC, and 1 on pouchitis (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were classified by type of IBD in order to pool data and perform the statistical meta‐analysis; therefore, the pouchitis study was excluded from the meta‐analysis. Of the CD studies, 32 evaluated switching from IFX to ADA, 4 switching from IFX to CZP, and 1 switching from ADA to IFX . All UC studies evaluated switching from IFX to ADA.…”
Section: Resultsmentioning
confidence: 99%
“…De Bie et al [35] found no differences in remission or failure rates between patients who did and did not receive concomitant IMs at baseline (remission: 22 It should be emphasized that these retrospective cohort studies and the above-mentioned post hoc analysis are severely biased due to 'confounding-byindication', that is, patients with more severe disease may have been more likely on combination therapy, and thus even if combination therapy was more effective, it just leveraged the outcome to those of the milder patients on monotherapy.…”
Section: Combination Therapy With Immunomodulators Versus Monotherapymentioning
confidence: 99%
“…In the relatively small pediatric studies on ADA use, serious or unusual infections were seen in 8 out of 290 (2.75%) patients: sepsis (n = 3), a severe case of Clostridium difficile, and abscess formation (n = 4) [23][24][25][26][31][32][33]35].…”
Section: Drug Profilementioning
confidence: 99%
See 1 more Smart Citation